INCREASING GENERATION AWARENESS FOR ANTI-CORUPTIVE ACTION WITH CASE STUDY (ARDIAN NOERVIANTO) - Fajriatunnisa; Futri Imelda Latifah; Mouza Septi Pratama; Siti Nazwa Fauziah; Nabila Putri Sahri Ramadhan; sevyanda mulyadi, bunga nazwa (DE'RECHTSSTAAT, 2023)
This tittle of this article is increase the young generation legal awarners to developing anti corruption behaviour through anti corruption education which is basically based on research about the student of faculty of Law Legal Awareness to Developing Anti Corruption Behavior in 2016. In general, the article discuss the problems of young generation knowledge about corruption, the corruption forms and anti corruption forms also about the young generation legal awareness to developing the anti corruption behavior. The empiric methods with the factual and concept approach use to solve those problems and describe in analytic description. The result of the research is young generation have a good knowledge about corruption, the forms of corruption and the forms of anti corruption from the simplets to the harder but this good knowledge did not followed by their legal awareness to developing anti corruption behavior. It means there is a weakness in the young generation mentally to developing anti corruption behavior. This situation describing the needed of anti corruption education for the young generation. Hopefully trhough the education will increase the young generation legal awareness to developing anti corruption behavior.